2009
DOI: 10.3168/jds.2008-1590
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for increased rates of sole ulcers, white line disease, and digital dermatitis in dairy cattle from twenty-seven farms in England and Wales

Abstract: Claw lesion treatment records were recorded by farmers on 27 dairy farms (3,074 cows, 36,432 records) in England and Wales between February 2003 and February 2004. These were combined with farm environment and management data collected using a combination of direct observations, interviews with farmers, and milk recording data. Multilevel models were constructed for the 3 most frequently reported lesions related to lameness, namely, sole ulcers, white line disease, and digital dermatitis. Risks associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 29 publications
9
87
0
4
Order By: Relevance
“…The prevalence of infectious and non-infectious claw disorders increased together with parity in both herd types, a finding consistent with earlier studies (Bielfeldt et al, 2005;Somers et al, 2005b;Holzhauer et al, 2008;Barker et al, 2009;Kujala et al, 2009Kujala et al, , 2010. The cumulative effect of physiological stress caused by multiple lactations and previous diseases, especially claw disorders, might predispose older cows to new claw disorders (Liinamo et al, 2009).…”
Section: Breed and Paritysupporting
confidence: 73%
See 2 more Smart Citations
“…The prevalence of infectious and non-infectious claw disorders increased together with parity in both herd types, a finding consistent with earlier studies (Bielfeldt et al, 2005;Somers et al, 2005b;Holzhauer et al, 2008;Barker et al, 2009;Kujala et al, 2009Kujala et al, , 2010. The cumulative effect of physiological stress caused by multiple lactations and previous diseases, especially claw disorders, might predispose older cows to new claw disorders (Liinamo et al, 2009).…”
Section: Breed and Paritysupporting
confidence: 73%
“…Previous L studies have also suggested that claw health might improve with access to pasture because of the more comfortable surface for lying down or standing (Hernandez-Mendo et al, 2007;Barker et al, 2009). For example, Barker et al (2009) reported that cows kept indoors 24 hours a day had a higher risk of sole ulcer and white line disease than cows grazing 24 h a day.…”
Section: Outdoor Accessmentioning
confidence: 93%
See 1 more Smart Citation
“…One hypothesis for this association is that underlying pathology carries over from one lactation to the next, making future cases more likely. The increase in lameness prevalence or risk with increasing parity that is widely reported would support this hypothesis (Barker et al, 2009;Randall et al, 2015;Solano et al, 2015). In addition, Newsome et al (2016) demonstrated that bone development on the caudal aspect of the distal phalanx at slaughter was positively associated with claw horn lesions during life, providing evidence for underlying pathology being associated with previous lameness.…”
mentioning
confidence: 58%
“…Different studies provided numbers on reduction of foot disorders by improving design and bedding of cubicles (e.g. Philipot et al, 1994;Barker et al, 2009). …”
Section: Estimating Effects Of Intervention Measuresmentioning
confidence: 99%